A97 QUALITY OVER QUANTITY: THE ASSOCIATION BETWEEN QUALITY OF REFERRALS RECEIVED BY IBD SPECIALISTS AND PATIENT OUTCOMES. (15th March 2019) - Mathias, H; Heisler, C; Morrison, J B; Currie, B; Phalen-Kelly, K; Jones, J
Abstract: Background: Most speciality inflammatory bowel disease (IBD) care can only be accessed through a referral. Timely access to specialty care has been associated with improved disease-related outcomes. To receive appropriate care, the referral needs to include high quality information. To date, no research has explored the association between referral quality and IBD patient outcomes. Aims: The study objectives were to determine if the quality of referrals to a collaborative IBD program influenced triage accuracy, wait times, and patient outcomes. Methods: 200 referrals to a collaborative IBD program in Nova Scotia, Canada for patients with confirmed or suspected IBD were reviewed. Referral quality was evaluated as low, moderate or high quality using an evidence and consensus-based metric. The association between referral quality and patient outcomes (wait time, hospitalizations, disease flares and additional referrals) was assessed using multivariate regression analysis. Results: The majority of referrals for IBD speciality care received by the program were categorized as being low quality. The findings of this study also suggest that quality of referral influences wait times and patient outcomes including disease flares and IBD-related hospitalizations. In particular, we noted that moderate-high quality referrals that included a diagnosis, were legible, were sent by GIs, nurse practitioners or emergency room physicians, had shorter wait times. Low quality referrals were associated with longer wait times. Additionally, we noted that patients who had referrals that included a diagnosis and were legible had fewer disease flares and IBD-related hospitalizations than referrals that did not included this information, presumably due to shorter wait time. Conclusions: Patients with a low quality referral to IBD speciality care may experience longer wait times and increased healthcare resource utilization than patients with higher quality referrals. Improvements in referral-based communication and content quality are needed. Defining minimum referral quality expectations and facilitation of high quality referrals through the development of standardized referral forms could be a solution to this problem. Specialist recommendations for first-line investigations and treatments for IBD patients waiting to be seen in post-triage communication to referring physicians could reduce healthcare resource utilization. Funding Agencies: None